PENGARUH WORK LIFE BALANCE, KOMPENSASI DAN STRES KERJA TERHADAP KINERJA KARYAWAN - Avri Lingga Puja; Irma Idayati; Pemas Febriansyah; Muhamad Azimi; Ikrom Syafira; Kevin Pratama Putra; Ahmad Mustaqim; Nanda Fikri Andika (PT. Hasba Edukasi Mandiri, 2026)
This study aims to determine the effect of work-life balance, compensation, and job stress on employee performance. The method used is a literature review by examining 26 articles from relevant previous research. The results of the study indicate that work-life balance and compensation have a positive effect on employee performance, because work-life balance and adequate rewards can increase employee motivation, focus, and productivity. Meanwhile, work stress has a negative effect on performance, because high work pressure can hinder concentration and reduce productivity. Overall, improving performance requires support for work-life balance, adequate compensation, and good work stress management.